THE INFOGRAPHIC PROJECTS IN SPEAKING ACTIVITIES - Dewanti Ratna Pertiwi; Maria Asumpta Deny Kusumaningrum (Universitas Sarjanawiyata Tamansiswa, 2021)
There are a lot of factors determining the success of learning process. Leaning media is one of them that can contribute to the excellent learning process. In this digital era, infographic either digital or printed is regarded as a suitable media for speaking as it is able to help students to present effectively. The combination of brief information in points and graphics helps the students in delivering particular topics to the audience that also develops the students’ speaking skill. The infographic in this research was conducted in projects for mechanical engineering students. The topic chosen for the research was ‘describing the excellence of a city’. It is one of the topics written in the curriculum for English 1 subject. The research applied a case study in which the data collection was gathered using observation, interview, and questionnaires. The results indicated that the infographic project could facilitate the speaking activities. The students showed positive responses in creating infographic, working in group project-based learning (PBL), and presenting the infographic content. These conditions indicate that the infographic project was successfully employed to facilitate the students’ speaking activity.